Peran Apoteker dalam Meningkatkan Pelayanan Kesehatan Di Puskesmas - Idris, Viviana; Ahmad, Islamudin (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2024)
The role of pharmacists in community health centers has a major impact on the provision of primary health services. This discussion explores the significance of pharmacists' contributions to patients, health workers, and the national health system. Pharmacists not only administer medications, but also play a key role in disease prevention, patient education, and collaboration with the healthcare team. However, there are factors that can hinder the role of pharmacists, including limited resources, complex regulations, and public perception. Public awareness, simpler regulations, and efficient resource management are the keys to optimizing the contribution of pharmacists in community health centers. In an effort to achieve quality primary health services, interprofessional collaboration and professional development of pharmacists are needed. The conclusion of this discussion emphasizes the importance of increasing the role of pharmacists as integral health agents, who not only focus on aspects of treatment, but also on preventing disease and improving overall public health. Thus, increasing the role of pharmacists in community health centers is expected to contribute significantly to efforts to provide holistic and affordable health services.